Língua, linguagem e fala: um estudo de conceitos basilares - Schio, Kaliandra Luiza Dalvit (2023)
The main aim of this research is to study the concepts of Language (langue), Language (langage) and Speech (parole) that have been established over the years, mainly by Ferdinand de Saussure and Émile Benveniste. Considering the constitution of Linguistic Science, it is very important to understand the role and distinction between each of the concepts mentioned, so we dedicate ourselves to the theoretical study of these concepts in order to extend our knowledge in the field of enunciative studies. Based on the definition of these concepts founded by the linguists, the basic research takes perspective on Benveniste’s Enunciation Theory to understand the problem of how Language (langue), Language (langage) and Speech (parole) are characterized, referring to enunciation and its influence on discourse studies and contributing to reflections and discussions about the importance of studies in the analysis of language in operation. The research’s main theoretical framework is centered on Ferdinand de Saussure’s reflections, especially those present in the Course in General Linguistics (2012), and Émile Benveniste’s Problems in General Linguistics I (1991) and II (1989). The bibliographic research will be exploratory in nature with a qualitative approach, as the subject of the study needs to be understood in depth for future linguistic analysis.